PROBLEMATIKA DAN PERLINDUNGAN HUKUM E-COMMERCE DI INDONESIA - Erie Hariyanto (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
One of the developments of information technology,telecommunication and computer is appearing the creation oftransaction model that is not necessary to meet directly or faceto face. The transaction is enough to do by using the electronicmedia that is internet media. In the transaction of e-commerce,many law problems develop that need a law arrangementbriefly and clearly as a guarantee of the law protection for thepeople involved. This article tries to answer this problem bygiving some alternative solutions in order to make the assurancelaw in e-commerce transaction formed.